New records of Ascomycetes from the Tropical Montane Cloud Forests of eastern Mexico - Raymundo, Tania; Valenzuela, Ricardo; Ramírez-Martínez, Julio Cesar; Martínez-Pineda, Michelle; Villagrán, Aurora Cobos; Trejo-Arana, Andrea; Sánchez-Flores, Marcos; Gay-González, Alfonso D.; Luna-Vega, Isolda (Phytotaxa, 2020)
The tropical montane cloud forest is an important reservoir of the diversity of Mexican ascomycetes. We cite and describe 17 species that had not been recorded in this vegetation type. Fifteen of them are new records for Mexico. Some of these species are associated with angiosperms and some with other fungi. Ongoing efforts are required to carry out floristic, taxonomic, phylogenetic and ecological studies of this group of fungi in such a diverse ecosystem that is cataloged as threatened.